Union Territory of Chandigarh Draft Annual Plan 2003-04 Volume - II (Statistical Portion) - Planning Commission (Planning Commission, 2003)
Draft annual plan -2003- 2004 - proposed outlays, physical targets and achievements, draft annual plan (2003-04) proposals for spillover & ongoing programmes/projects as in annexure, draft annual plan 2003-2004 - proposals for programmes/projects - new schemes, centrally sponsored : scheme, draft annual plan 2003-04-pradhan mantri gramm udyog yojana-outlay/expenditure, draft annual plan 2003-04-proposed outlays financial outlays/expenditure for voluntary sector, women component (EC) in the state plan programmes - I draft annual plan 2003 - 2004 : financial outlays, women component (WC) in the state plan programmes-ii draft annual plan 2003-2004-physical targets
Finance Department Planning and Evaluation Organisation Chandigarh Administration